STRUCTURAL FEATURES OF DECIDUOUS TEETH IN CHILDREN OF TRANSCARPATHIAN REGION - Klitynska, O.V.; Shetelya, V.V.; Yeroshenko, G.A.; Zorivchak, T.I.; Struk V.І.; Kotyk, T.L.; Popadynets, O.G. (World of Medicine and Biology, 2021)
Prevention of dental caries of permanent teeth in children is one of the topical problems of the contemporary pediatric dentistry, caused by the high prevalence and intensity of this disease. Oral examination of children of different ages in the regions of Ukraine shows a significant increase of the incidence of dental caries of both deciduous and permanent teeth in recent years. Three stages of the reaction in the pulp and dentin can be distinguished in lowering of the protective function of enamel caused by insufficient mineralization of deciduous teeth: infiltration by immunocompetent cells of a subodontoblastic Weil’s layer, local cytotoxic destruction of the layer of odontoblasts and diapedesis of lymphocytic elements into the dentinal tubules. The latter phenomenon leads to their blockage and subsequent disturbance of circulation of dental liquor in the centrifugal direction that in turn will cause disturbance of trophism not only in dentin, but also in enamel.